Master class with András Keller Verbier Festival 2018 - Bartók, Béla 1881-1945; Brahms, Johannes 1833-1897; Brahms, Johannes 1833-1897; Brahms, Johannes 1833-1897; Brahms, Johannes 1833-1897 (DakApp, 2018)
2018 marked the 25th anniversary of the Verbier Festival, an exciting milestone for Verbier's artists and audiences alike! For the first time, we brought you closer to the musicians than ever before with ten master classes led by incredible artists, including Barbara Frittoli, Thomas Quasthoff, the Quatuor Ébène, Richard Goode and others